On the political ontology of making things up in political ecology critique: An engagement with Bormpoudakis (2019) and Knudsen (2023) - Sian Sullivan (Journal of Political Ecology)
I engage with two recent articles published in the Journal of Political Ecology, both of which critique political ecology engagements with ontological and epistemological complexities. These complexities might be distilled into the idea that how 'the world' is socially known also shapes how the world is known to be. I explore three key issues worked through in these papers, partly with reference to work of mine, namely: 1) conservation struggles around biodiversity offsetting; 2) debates regarding plural and relational ontologies, particularly representations of 'flatness' and 'depth' in ontological considerations; and 3) critical realism, specifically distinctions between perspectives on transitive and intransitive dimensions in qualifying understandings of reality. I highlight a pernicious problem of dismissive approaches towards analysts trying to ask difficult and subtle questions about 'onto-epistemology.' This situation seems surprising given the effort in political ecology towards recognising and respecting plural knowledges, particularly knowledges often overridden by discourses emboldened by structures of power. My overall aim is towards clarity in ongoing political ecology debate on these issues, alongside the pursuit of respectful praxis in this burgeoning area of engagement.